ANALISIS NETWORKING DALAM IMPLEMENTASI KEBIJAKAN PERLINDUNGAN PEREMPUAN DAN ANAK - Resa Septia Nugroho; Dewi Rostyaningsih; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Complexity of implementing policies to protect women and children in Semarang City cannot only be handled by Dinas Pemberdayaan Perempuan dan Perlindungan Anak (DP3A) as a representative of the local government, but also involving other parties. This study aims to determine the network of cooperation between actors in implementing policies to protect women and children from acts of violence in the city of Semarang. The MSN approach with networking elements from Kadji was chosen to analyze field findings and representing the data using a qualitative descriptive methods. The research results show that there are dynamics of strategic partnership sub-elements, synergy and symbiosis of mutualism. The findings of the dynamics of cooperation networks between actors are expressed by not optimal content of transparency of cooperative relations, there is no place to accommodate the aspirations of actors outside the institution, the collaboration that not optimal and comprehensive, the authority that overlap between actors, the issues on human resources, the funding allocation, and the fulfillment of other rights that are lacking obtained by actors outside the institutional structure. Follow-up actions that can be carried out by related policy actors include conducting a review of regional regulations by maximizing the existence of each actor involved, improving budget and human resource management, and establishing good relations between actors, especially actors outside the institution.